NF-κB System Is Chronically Activated and Promotes Glomerular Injury in Experimental Type 1 Diabetic Kidney Disease - Foresto-Neto, Orestes; Albino, Amanda Helen; Arias, Simone Costa Alarcon; Faustino, Viviane Dias; Zambom, Fernanda Florencia Fregnan; Cenedeze, Marcos Antonio; Elias, Rosilene Motta; Malheiros, Denise Maria Avancini Costa; Camara, Niels Olsen Saraiva; Fujihara, Clarice Kazue; Zatz, Roberto (Frontiers in Physiology, 2020)
High glucose concentration can activate TLR4 and NF-κB, triggering the production of proinflammatory mediators. We investigated whether the NF-κB pathway is involved in the pathogenesis and progression of experimental diabetic kidney disease (DKD) in a model of long-term type 1 diabetes mellitus (DM). Adult male Munich-Wistar rats underwent DM by a single streptozotocin injection, and were kept moderately hyperglycemic by daily insulin injections. After 12 months, two subgroups – progressors and nonprogressors - could be formed based on the degree of glomerulosclerosis. Only progressors exhibited renal TLR4, NF-κB and IL-6 activation. This scenario was already present in rats with short-term DM (2 months), at a time when no overt glomerulosclerosis can be detected. Chronic treatment with the NF-κB inhibitor, pyrrolidine dithiocarbamate (PDTC), prevented activation of renal TLR4, NF-κB or IL-6, without interfering with blood glucose. PDTC prevented the development of glomerular injury/inflammation and oxidative stress in DM rats. In addition, the NF-κB p65 component was detected in sclerotic glomeruli and inflamed interstitial areas in biopsy material from patients with type 1 DM. These observations indicate that the renal NF-κB pathway plays a key role in the development and progression of experimental DKD, and can become an important therapeutic target in the quest to prevent the progression of human DKD.